Correlation between the Degree of Esophageal Varices and Liver Stiffness in Liver Cirrhosis Patients - Femmy Nurul Akbar; Tjahjadi Robert Tedjasaputra; Dadang Makmun; Nurul Akbar (The Indonesian Society for Digestive Endoscopy, 2009)
Background: Bleeding due to rupture of esophageal varices is one of main cause of death in liver cirrhosis, that endoscopy screening is recommended. However endoscopy is invasive and frequently cannot be performed due to contraindication, high-cost or uncomfortable effect to the patients, particularly on patients have not had any bleeding before. Consequently, it is necessary to find other assessment which can predict the presence of esophageal varices. Recent studies found liver stiffness measurement by the liver transient-elastography is one of non invasive measurement to evaluate liver fibrosis.This study was designed to know the correlation between degree of the esophageal varices and the degree of liver stiffness. Method: This was cross sectional study. Liver cirrhosis patients were consecutively enrolled in this study. They underwent endoscopy to determine esophageal varices and subsequently the liver transient- elastography by Fibroscan technique to determine liver stiffness. Degree of the esophageal varices based on OMED criteria. Liver stiffness are expressed in kilopascal (kPa). Correlation analysis was done to assess this study. Result: There were 13 subjects. Most subjectswere male, age 50 years and Child-Pugh A or B. The mean value of liver stiffness was 35.55 ± 23.60 kPa and mean OMED was 5.61 ± 2.14. The coefficient correlation between degree esophageal varices and degree liver stiffnes was 0.492, p = 0.087. Conclusion: There is moderate correlation but not statistically significant between the degree of liver stiffness and the degree of esophageal varices. Larger sample size is necessary to find the correlation between the degree of liver stiffness and esophageal varices. Keywords: liver cirrhosis, degree of esophageal varices, liver stiffness